Etika Islami dalam Berkomentar di Instagram @Taubatters: Kajian Terhadap Fatwa Mui tentang Muamalah di Media Sosial - Ramadhani, M. Kelfin Gilang (STAI Publisistik Thawalib Jakarta, 2024)
The widespread use of social media, particularly Instagram, poses new challenges in maintaining ethical communication and commenting practices, especially in the context of Islamic values. This research aims to analyze commenting practices on social media considering Islamic ethical values and the Indonesian Ulema Council (MUI) Fatwa on social interactions on the Instagram account @taubatters. The research methodology employed qualitative analysis through document analysis. Data collection techniques involved documentation, and data processing utilized reduction, data presentation, and conclusion drawing. The findings indicate that while most comments on the Instagram account @taubatters reflect Islamic muamalah principles according to the MUI Fatwa, emphasizing faith, piety, and moral values in social media interactions, the analysis also reveals comments that violate these principles, such as backbiting, slander, spreading discord, and bullying, contradicting Islamic teachings and potentially harming others. This underscores the complexity of social interactions in the digital world, where some adhere well to ethical practices while others have yet to fully embrace existing moral guidelines.